Problems of development and allocation of productive forces in mono-towns in Kazakhstan - Tazhybekova, M. G. (Journal of Economic Research & Business Administration, 2015)
The article is about the development problems of mono-towns of Kazakhstan and their solutions through the effi cient allocation of productive forces. Since tenth of the total production in Kazakhstan is located in these towns, the development of mono-towns affects the formation of urban areas and growth points. It focuses on the implementation of the state program of mono-towns, shows the pros and cons of this program and solutions. The article contains t he defi nition of mono-towns and especially economic development, put forward the way the distribution of productive forces, in accordance with these features. Effi cient allocation of productive forces in mono-towns is not only addressing the economic, social, demographic and environmental problems, but also we have to look out for innovative and educational factors of development.